KUALITAS INFORMASI PELANGGAN DALAM RANGKA PENINGKATAN KEPUASAN DAN LOYALITAS PELANGGAN PADA PT AKUR PRATAMA CABANG C - M. Ardi Nupi; Elsa Sundari; Mira Santiani; Rian Oktavian (IKOPIN, 2019)
A business that is engaged in retail is a promising business for entrepreneurs. Not surprisingly, at this time retail businesses are mushrooming in various regions in Indonesia. Its mushrooming presence does not make this business devoid of customers due to endless human needs. In meeting their needs, a person will decide to shop at a place in accordance with his wishes and tastes, both from the distance of the place, the price of goods, the quality of goods, the quality of the place and the quality of service. From the various choices above it makes one of the reasons why someone decides to shop at the place he wants. Therefore, now many companies are trying to develop effective strategies to build, maintain and increase customer loyalty, one of which is PT Akur Pratama. This study aims to determine the quality of customer information in order to increase customer satisfaction and loyalty. This research was conducted at one retail company PT Akur Pratama Branch C, located in the Bandung area. Data collection methods in this study with a questionnaire with. The number of samples used in this study were 30 respondents / consumers. PT Akur Pratama Branch C customer information service has not been satisfying so far so that its customers are not fully satisfied and loyal. Some of the problems faced by PT Akur Pratama Branch C are not prioritizing the interests of consumers, the service is not appropriately and quickly according to the promised time, is not quick enough to respond to problems raised by consumers, and is not always alert and ready when there are consumers who ask for help